Nickel-Based Alloys

The nickel-based alloy composition, optimized with specific elemental ranges, addresses the challenges of processing and high-temperature performance in additive manufacturing, achieving enhanced strength, corrosion resistance, and additive manufacturing capabilities.

JP7670484B2Active Publication Date: 2025-04-30OXMET TECH LTD

Patent Information

Application Number
JP2020526700
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-07-28
Filing Date
2018-07-27
Publication Date
2025-04-30
Estimated Expiration
2038-07-27

AI Technical Summary

Technical Problem

Existing nickel-based superalloys face challenges in additive manufacturing due to limitations in ease of processing and achieving high-performance material properties, particularly at high temperatures.

Method used

A nickel-based alloy composition with specific ranges of elements such as aluminum, titanium, niobium, tantalum, tungsten, molybdenum, cobalt, chromium, carbon, boron, zirconium, rhenium, ruthenium, and nickel, optimized to satisfy certain weight percentage equations, enhancing both strength and additive manufacturing capabilities.

Benefits of technology

The alloy composition achieves a balance of high strength, corrosion resistance, and improved additive manufacturing processability, with enhanced creep resistance and temperature strength exceeding 650°C, while maintaining a good balance of material cost and density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670484000041
    Figure 0007670484000041
  • Figure 0007670484000042
    Figure 0007670484000042
  • Figure 0007670484000043
    Figure 0007670484000043
Patent Text Reader

Abstract

The composition, by weight, is 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% iridium. 1. A nickel-base alloy composition comprising: nickel, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, wherein the composition satisfies the following formula: 4.2≦(W W +0.92W Re +1.58W Ru )+W Mo W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦4.0 and 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) In the above formula, W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy. [Selected Figure] Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nickel-base superalloy compositions designed for application in additive manufacturing (AM) processes, including, but not limited to, powder-bed based AM methods (e.g., selective laser melting, electron beam melting) and direct metal deposition methods (e.g., powder deposition and wire-based methods). [Background technology]

[0002] Metal AM is emerging as a new manufacturing method that can bring many benefits, such as increasing component complexity, just-in-time production, and reduced material waste. However, as the processing technology matures, the focus has been on the development of new metal alloys designed to overcome one of the most important limitations of the process, specifically the combination of ease of processing with high-performance material properties. In recent years, there has been a trend to transfer nickel-based superalloys, which can be produced in cast or wrought forms, to AM processing. However, this has proven to be largely inappropriate, since many of the material properties required for ease of processing in AM processing are not satisfied by such alloys, resulting in materials that are very difficult to process and that do not have the expected structural integrity.

[0003] Table 1 lists a number of examples of nickel-base superalloy compositions that are widely used in commercial applications.

[0004] [Table 1]

[0005] These materials are used in many industries, including aerospace, power generation, chemical processing, and oil and gas, to produce corrosion-resistant parts that maintain high strength at high temperatures. They contain as many as 10 different alloying elements required to impart the desired combination of properties. However, in many of these alloys, the combination of elements applied limits the ability of the material to be processed by AM; in others, it limits the strength that can be achieved. It would be desirable to find alloys with an improved combination of strength and ability to be processed by AM. In addition, it would be desirable to manage tradeoffs in other properties, such as creep resistance, density, cost, and corrosion resistance. Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide a nickel-based alloy suitable for the production of high strength, corrosion resistant engineered parts via AM processing, especially for applications requiring high temperature strength above 650°C (tensile strength, creep strength), which combines a good balance between material cost and density. [Means for solving the problem]

[0007] The first embodiment of the present invention is a sintered body containing, by weight percentage, 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% indium. The present invention provides a nickel-based alloy composition comprising rhodium, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, which satisfies the following formula: 4.2≦(W W +0.92W Re +1.58W Ru )+W Mo W Al +0.5W Ti +0.3W Nb +0.15W Ta <=4.0 and 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) In the above formula, W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy.

[0008] A second embodiment of the present invention is a sintered material that contains, by weight percentage, 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% indium. The present invention provides a nickel-based alloy composition comprising rhodium, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, which satisfies the following formula: 4.2≦W W +W Mo W Al +0.5W Ti +0.3W Nb +0.15W Ta <=3.5 and 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) In the above formula, W Nb , W Ta , W Ti , W Mo , and W Al are the weight percentages of niobium, tantalum, titanium, molybdenum, and aluminum, respectively, in the alloy.

[0009] A third embodiment of the present invention is a sintered body comprising, by weight percentage, 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% indium. The present invention relates to a nickel-based alloy composition comprising rhodium, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, and which satisfies the following formula: 4.2≦(W W +0.92W Re +1.58W Ru )+W Mo W Al +0.5W Ti +0.3W Nb +0.15W Ta <=3.5 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) and W W +W Mo <= 4.2 In the above formula, W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy.

[0010] A fourth embodiment of the present invention is a sintered body comprising, by weight percentage, 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% indium. The present invention relates to a nickel-based alloy composition comprising rhodium, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, and which satisfies the following formula: 4.2≦W W +W Mo 3.5≦W Al +0.5W Ti +0.3W Nb +0.15W Ta <=4.0 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) In the above formula, W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy.

[0011] A fifth embodiment of the present invention is a sintered body comprising, by weight percentage, 1.0 to 3.5% aluminum, 0.0 to 3.6% titanium, 0.0 to 6.0% niobium, 0.0 to 4.9% tantalum, 0.0 to 5.4% tungsten, 0.0 to 4.0% molybdenum, 8.9 to 30.0% cobalt, 10.8 to 20.6% chromium, 0.02 to 0.35% carbon, 0.001 to 0.2% boron, 0.001 to 0.5% zirconium, 0.0 to 5.0% rhenium, 0.0 to 8.5% ruthenium, and 0.0 to 4.6% indium. The present invention relates to a nickel-based alloy composition comprising rhodium, 0.0-0.5% vanadium, 0.0-1.0% palladium, 0.0-1.0% platinum, 0.0-0.5% silicon, 0.0-0.1% yttrium, 0.0-0.1% lanthanum, 0.0-0.1% cerium, 0.0-0.003% sulfur, 0.0-0.25% manganese, 0.0-6.0% iron, 0.0-0.5% copper, 0.0-0.5% hafnium, and the balance being nickel and unavoidable impurities, and which satisfies the following formula: 4.2≦(W W +0.92W Re +1.58W Ru )+W Mo 3.5≦W Al +0.5W Ti +0.3W Nb +0.15W Ta <=4.0 3.0≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) and W W +W Mo <= 4.2 In the above formula, W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy.

[0012] All further limitations relating to the first aspect (or any other aspect) disclosed herein are equally applicable to the second and / or third and / or fourth and / or fifth aspects.

[0013] These alloys offer a previously unattainable balance of strength and additive manufacturability.

[0014] As used herein, the term "consisting of" refers to 100% of a composition and is used to exclude the presence of additional components so that the percentage is 100%. Unless otherwise stated, percentages are expressed as weight percentages.

[0015] The present invention will now be more fully described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows the calculated tradeoff between yield strength (in terms of the Strength Merit Index) and ease of processing by additive manufacturing (in terms of the AM Index) within the alloy design space described in Table 2. [Diagram 2] Figure 2 is a contour plot showing the effect of Al and Ti on the cracking susceptibility of a nickel-base superalloy during welding (modified from M Prager, CS Shira, Welding Research Council Bulletin, pp 128, (1968)). [Diagram 3] FIG. 3 is a contour plot showing the effect of the sum of the elements Aluminum and Titanium on the x-axis and the sum of the elements Niobium and Tantalum on the y-axis on yield strength (in terms of the Strength Merit Index), with the preferred limit for the AM Merit Index (MAdditive-Manufacture ≧−1.0) superimposed. [Figure 4]FIG. 4 is a contour plot showing the effect of tungsten and tantalum elements on alloy density in alloys with favorable AM ​​index (MAdditive-Manufacture≧0). [Diagram 5] FIG. 5 is a contour plot showing the effect of molybdenum and tungsten on solid solution strengthening (in terms of solid solution index) in alloys with favorable AM ​​index (MAdditive-Manufacture≧0). [Figure 6] FIG. 6 is a contour plot showing the effect of the sum of the elements aluminum and titanium on the x-axis and the sum of the elements niobium and tantalum on the y-axis on the volume fraction of γ' at 900 °C, with different values ​​of the AM merit index superimposed. [Figure 7] FIG. 7 is a contour plot showing the effect of γ' volume fraction and creep merit index on the predicted 1000 hour creep life at 137 MPa, with potential limits on γ' volume fraction and creep merit index within the scope of the present invention superimposed. [Figure 8] FIG. 8 is a contour plot showing the effect of cobalt and tungsten on creep resistance (in terms of creep merit index) for alloys with favorable AM ​​index (MAdditive-Manufacture ≧0) when the molybdenum content is fixed at 1.0 wt.%. [Figure 9] FIG. 9 is a contour plot showing the effect of cobalt and tungsten on creep resistance (in terms of creep merit index) for alloys with favorable AM ​​index (MAdditive-Manufacture ≧0) when the molybdenum content is fixed at 2.0 wt.%. [Figure 10]FIG. 10 is a contour plot showing the effect of cobalt and tungsten on creep resistance (in terms of creep merit index) for alloys with favorable AM ​​index (MAdditive-Manufacture ≧0) when the molybdenum content is fixed at 3.0 wt.%. [Figure 11] FIG. 11 is a contour plot showing the effect of cobalt and tungsten on creep resistance (in terms of creep merit index) for alloys with favorable AM ​​index (MAdditive-Manufacture ≧0) when the molybdenum content is fixed at 4.0 wt.%. [Figure 12] FIG. 12 shows the effect of chromium content and aluminum content on the main oxides formed during the oxidation process, with the maximum and minimum aluminum contents for the present invention superimposed. [Figure 13] FIG. 13 is a contour plot showing the effect of the sum of the elements molybdenum and tungsten, and chromium, on the microstructural stability (in terms of the stability value Md) in alloys with favorable AM ​​index (MAdditive-Manufacture≧0). [Figure 14] Figure 14 shows a micrograph of a nickel-base superalloy produced using powder bed-based AM processing. The influence of the AM merit index on the susceptibility to cracking during the AM process is evident, supporting the preferred limit of the AM merit index within the scope of the present invention (MAdditive-Manufacture >= -1.0). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Traditionally, nickel-base superalloys have been designed on an empirical basis. Thus, their chemical compositions have been found using time-consuming and expensive experimental development involving small-scale processing on limited amounts of material and subsequent characterization of behavior. The alloy compositions employed are those found to exhibit the best or most desirable combination of properties. The large number of alloyable elements indicates that these alloys are not fully optimized and that improved alloys likely exist.

[0018] In superalloys, chromium (Cr) and aluminum (Al) are typically added to provide oxidation / corrosion resistance, and cobalt (Co) is added to improve resistance to sulfidation. For creep resistance, molybdenum (Mo), tungsten (W) and cobalt (Co) are introduced because they disrupt thermally activated processes such as dislocation climb, which determine the rate of creep deformation. For static and cyclic strength, aluminum (Al), tantalum (Ta), niobium (Nb) and titanium (Ti) are introduced because they promote the formation of a precipitation hardening phase, gamma prime (γ'), which is coherent with the face-centered cubic (FCC) matrix phase called gamma (γ).

[0019] Here we describe a model-based approach used to find new grades of nickel-base superalloys, which we refer to as the "Alloys-By-Design" (ABD) method. This approach uses a framework of computational materials models to estimate design-relevant properties over a very wide compositional range. This alloy design tool allows, in principle, to identify the optimal alloy composition that satisfies a given set of design constraints, solving the so-called inverse problem.

[0020] The first step in the design process is to define the list of elements along with associated upper and lower compositional limits. The compositional limits for each added element considered in this invention, called the "alloy design space", are listed in Table 2.

[0021] [Table 2] The balance is nickel. The levels of carbon, boron and zirconium were fixed at 0.06%, 0.01% and 0.006%, respectively. These elements are known to be advantageously present to provide strength at grain boundaries.

[0022] The second step utilizes thermodynamic calculations, which are used to calculate phase diagrams and thermodynamic properties for a specific alloy composition. Often this is called the CALculate PHAse Diagram (CALPHAD) method. These calculations are performed at typical service temperatures for the new alloy (900°C) and provide information on phase equilibria (microstructure).

[0023] The third step is to find an alloy composition with the desired microstructure. For nickel-base superalloys that require good resistance to creep deformation, creep rupture life generally improves as the volume fraction of the precipitation hardening phase γ' increases. The most beneficial range of γ' volume fraction is 60%-70% at 900°C (although other design constraints often limit the volume fraction to lower values). At values ​​of γ' volume fraction greater than 70%, a decrease in creep resistance is observed.

[0024] Also, the magnitude of the γ / γ' lattice misfit is limited because it must be small, either positive or negative, otherwise coherency is lost. The lattice misfit δ is defined as the mismatch between the γ and γ' phases and is determined according to the following equation: JPEG0007670484000003.jpg22170 Here, α γ and α γ’ are the lattice constants of the γ and γ' phases.

[0025] Thus, the model is calculated to find all compositions within the design domain that have a lattice mismatch γ' less than a given amount and result in a desired volume fraction of γ'.

[0026] The fourth step is to estimate indices of merit for the remaining alloy compositions found in the dataset. Examples of these include creep indices of merit (representing an alloy's creep resistance based on average composition only), strength indices of merit (representing an alloy's precipitation yield strength based on average composition only), solid solution indices of merit (representing an alloy's solid solution yield strength based on average composition only), density, and cost.

[0027] In the fifth stage, the calculated merit index is compared with the constraints for the required properties. These design constraints are considered as boundary conditions for the problem. All compositions that do not satisfy the boundary conditions are eliminated. At this stage, the size of the trial data set is reduced very significantly.

[0028] The sixth and final step is to analyze the dataset of remaining compositions. This can be done in a variety of ways. One approach is to screen the database for alloys that exhibit the highest values ​​of merit indices, such as lightest weight, best creep resistance, best oxidation resistance, lowest price, etc. Alternatively, one approach can use the database to determine the relative tradeoffs in performance that result from different combinations of properties.

[0029] Next, we explain seven examples of merit indexes.

[0030] The first merit index is the creep merit index. Comprehensive observations show that the time-dependent deformation (i.e. creep) of nickel-base superalloys occurs by dislocation creep, which is restricted to the gamma phase in the initial activation. Dislocation segments are therefore rapidly pinned at the gamma / gamma' interface due to the large fraction of gamma' phase. The rate-controlling step is then the departure of trapped configurations of dislocations from the gamma / gamma' interface, which depends on the local chemistry (in this case the composition of the gamma phase) which is the major influence of the alloy composition on the creep properties.

[0031] The load is single-axis <001> The rate of creep strain accumulation along the crystallographic direction To solve for JPEG0007670484000004.jpg4437, a physics-based microstructure model can be used. The set of equations is as follows: JPEG0007670484000005.jpg30159, where, JPEG0007670484000006.jpg3739 is the mobile dislocation density, and φ p is the volume fraction of the γ' phase and ω is the width of the matrix channel. The terms σ and T are the applied stress and temperature, respectively. The terms b and k are the Burgers vector and Boltzmann constant, respectively. The term JPEG0007670484000007.jpg29165 is a constraining factor that describes the close proximity of cubic grains in these alloys. Equation 3 describes the dislocation multiplication process, which requires an estimate of the multiplication parameter C and the initial dislocation density. Term D eff is the effective diffusivity that controls the climbing processes at the particle / matrix interface.

[0032] In the above, the composition dependence is expressed by two terms φ p and D eff Therefore, the microstructural architecture is assumed to be constant (it is mostly controlled by heat treatment) and φ p If is fixed, the dependence on chemical composition is D eff For the purposes of alloy design modeling described herein, it has been found that it is not necessary to perform a full integration of Equations 2 and 3 for each prototype of the alloy composition. Instead, the first order merit index M creep The primary merit index M creep is defined as follows: JPEG0007670484000008.jpg18165, where x i is the atomic fraction of solute i in the γ phase, JPEG0007670484000009.jpg4437 is a suitable mutual diffusion coefficient.

[0033] The second merit index is the strength merit index. In high nickel-based superalloys, most of the strength comes from the precipitate phases. Therefore, optimizing the alloy composition to maximize the precipitate strength is an important design consideration. From hardening theory, the strength merit index M strength has been proposed. The index considers the maximum possible precipitation strength, which is determined as the point at which the transition from weak to strong bond dislocation shearing occurs. The strength merit index M strength can be approximated using the following formula: JPEG0007670484000010.jpg20166 where, JPEG0007670484000011.jpg4437 is the Taylor factor, gamma APB is the antiphase boundary (APB) energy, φ p is the volume fraction of the γ' phase and b is the Burgers vector.

[0034] From equation 5, it is clear that the defect energy of the γ' phase, e.g., the APB energy, has a significant effect on the deformation behavior of nickel-based superalloys. It has been found that an increase in the APB energy improves mechanical properties such as tensile strength and resistance to creep deformation. Using density functional theory, the APB energies of many Ni-Al-X systems have been studied. From this work, the effect of third elements on the APB energy of the γ' phase was calculated, and a linear superposition of the effect of each third element addition was assumed when considering complex multi-component systems, resulting in the following equation: JPEG0007670484000012.jpg15169, where x Cr , x Mo , x W , x Ta , x Nb , and x Ti represent the concentrations in atomic percent of chromium, molybdenum, tungsten, tantalum, niobium, and titanium, respectively, in the gamma prime phase. The composition of the gamma prime phase is determined from phase equilibrium calculations.

[0035] The third merit index is the solid solution merit index. Solid solution hardening occurs in the (FCC) matrix phase called gamma (γ), and this hardening mechanism is particularly important at high temperatures. A model is adopted for the strengthening of the matrix phase, which assumes the superposition of individual solute atoms. The solid solution strengthening coefficients ki for the elements considered in the design space are 225, 39.4, 337, 1015, 1183, 1191, 775, and 977 MPa / at.% for aluminum, cobalt, chromium, molybdenum, niobium, tantalum, titanium, and tungsten, respectively. 1 / 2 The solid solution index is calculated based on the equilibrium composition of the matrix phase using the following formula: JPEG0007670484000013.jpg15169 Here, M solid-solutionis the solid solution merit index, and x i is the concentration of element i in the gamma matrix phase.

[0036] The fourth merit index is density. Density ρ was calculated using correction factors and simple rules of mixtures, where ρ i is the density of a particular element, x i is the atomic fraction of the alloying element. JPEG0007670484000014.jpg15169

[0037] The fifth merit index is cost. To estimate the cost of each alloy, a simple rule of mixtures was applied, where the weight fraction of the alloying element x i 2. Current (2016) raw material costs of alloying elements i was multiplied. JPEG0007670484000015.jpg15169

[0038] The estimates assume that processing costs are the same for all alloys, i.e., product yields are not affected by composition.

[0039] The sixth merit index is the Additive Manufacturing (AM) Index. The ability of an alloy to be processed by additive manufacturing is related to its chemical composition. The ability for AM is related to the criteria used to evaluate the ability to weld nickel superalloys ("weldability"). This index is developed from empirical observations relating alloy composition to the weldability of nickel-based superalloys (Figure 2). In this relationship, a factor of 0.5 is added to the titanium content, as titanium has approximately twice the density of aluminum, to convert this to an "aluminium equivalent". In effect, the additive manufacturing process of metal alloys is a continuous welding process. An adaptation of the above observations has been made that only relates weldability to the aluminum and titanium contents. A correction is included to account for the effect of tantalum and niobium, which behave similarly to aluminum and titanium during solidification. As with titanium, a constant is added to convert these elemental additions to "aluminium equivalents". Hence, niobium and tantalum have correction factors (determined from their densities relative to aluminum) of 0.3 and 0.15, respectively. The following formula applies to the AM Index:

[0040] JPEG0007670484000016.jpg15169Where, Al , W Ti , W Nb , and W Ta are the weight percentages of aluminum, titanium, niobium, and tantalum in the alloy. Lower values ​​of the AM Index indicate better response to additive manufacturing processing. AM Index values ​​of -1.0 or greater indicate satisfactory additive manufacturing performance (see FIG. 14 and associated discussion). Values ​​of -0.5 or greater, or even 0 or greater, are preferred, as they indicate ease of processing by additive manufacturing.

[0041] The seventh merit index is based on the elimination of candidate alloys based on unsuitable microstructural architecture, which is made based on the weakness of the TCP phase. To do this, the d-orbital energy levels (referred to as Md) of the alloying elements are used to determine the total effective Md level according to the following formula: JPEG0007670484000017.jpg15169, where x i represents the mole fraction of element i in the alloy. A large value of Md indicates a high probability of TCP formation.

[0042] Using the ABD methodology described above, the alloy composition of the present invention was discovered, whose design intent is to optimize the composition of a nickel-based alloy for producing high strength, corrosion resistant engineered articles via AM processing, especially for applications requiring high temperature strength (tensile strength, creep strength) above 650°C, combined with an excellent balance of material cost and density.

[0043] The material properties determined using the ABD method for typical compositions of conventional cast nickel-base alloys listed in Table 1 are listed in Table 3. The design of the new alloys took into consideration the predicted properties for these listed alloys.

[0044] Next, the rationale for the design of the new alloy is explained.

[0045] [Table 3]

[0046] As shown in Figure 1, there is a trade-off between alloy strength, as calculated by the Strength Merit Index, and the suitability of the alloy to be produced by AM, as calculated by the AM Merit Index (values ​​of the AM Merit Index below -1.0 mean that it is difficult to process). The locations of many commercially used and well-known nickel-base superalloys are depicted in this figure. It can be seen that as strength increases, it becomes more difficult to process. Figure 1 also shows millions of studied alloy compositions that fall within the compositional region (shaded area) listed in Table 2. Despite this trade-off, it has been shown that it is possible to obtain alloys with an improved balance of high strength combined with a greatly improved ability to be processed by AM. Finding alloy compositions that provide this beneficial effect is discussed in the next section.

[0047] Figure 3 shows the relationship between elemental additions that are primarily added to form the γ' phase and the calculated strength merit index. As stated in the AM merit index (Eq. 10), elements that form the γ' phase can reduce the ease of processing the alloy by AM. Therefore, the combination of these elements needs to be optimized to achieve the best balance between AM processability and strength. Plotted on the figure is a dotted line that indicates the limit at which the alloy is considered to be easily processable by AM, with elemental ranges above the line being less favorable as they limit the processing of the alloy. This line has the following formula:

[0048] JPEG0007670484000019.jpg15170Where, Al , W Ti , W Nb , and W Taare the weight percentages of aluminum, titanium, niobium, and tantalum, respectively, in the alloy. The additive manufacturing formula indicates that the maximum allowable level of aluminum is 4.0 wt%, but aluminum is known to increase the solvus temperature of the gamma prime phase. A low gamma prime solvus temperature is favorable for AM processability because it reduces strain accumulation in the build state. To achieve a low gamma prime solvus temperature, e.g., a maximum gamma prime solvus temperature of 1100°C, which would provide an alloy with a lower solvus than the range of alloys listed in Table 3 (Crudden et al. Acta Materialia 75 (2014) 356-370), the aluminum content is limited to 3.5 wt% or less. Preferably, the maximum concentration of aluminum is limited to 3.5 wt% (more preferably 3.0 wt%, or even 2.5 wt%, or 2.2 wt% to ensure good additive manufacturing). Meeting this formula means that the AM merit index is at least -0.5. The higher the AM merit index, the easier the AM process is. Al +0.5W Ti +0.3W Nb +0.15W Ta ≦3.4, more preferably W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦3.3, and even more preferably W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦3.2, and even more preferably W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦3.1, and most preferably W Al +0.5W Ti +0.3W Nb +0.15W Ta <=3.0.

[0049] The elemental additives titanium, niobium, and tantalum are added in place of elemental aluminum, and these elements partition into the γ' phase. If the combination of these elements (by atomic percentage) is significantly greater than the total aluminum content (by atomic percentage), the stability of the γ' phase may be reduced, resulting in the formation of undesired phases such as delta (δ) and eta (η). The proportions of the elements by atomic percentage are approximated by converting the weight percentages of the elements titanium, niobium, and tantalum in terms of their relative densities to aluminum, which are approximated to be 0.5, 0.3, and 0.15, respectively. Therefore, it is preferred that the ratio of the sum of the elements titanium, niobium, and tantalum to aluminum be kept below 1.5, so that the following formula is satisfied: JPEG0007670484000020.jpg18170

[0050] Thus, with a maximum allowable amount of Al of 3.5 wt%, titanium is limited to 3.6 wt%, niobium to 6.0 wt%, and tantalum to 12.0 wt%. To provide better stability of the gamma prime phase, more preferably the ratio of the sum of the elements titanium, niobium, and tantalum to aluminum is kept below 1.125. Thus, more preferably titanium is limited to 3.1 wt%, niobium to 5.1 wt%, and tantalum to 10.3 wt%. To provide better stability of the gamma prime phase, more preferably the ratio of the sum of the elements titanium, niobium, and tantalum to aluminum is kept below 1.00. Thus, more preferably titanium is limited to 3.0 wt%, niobium to 5.0 wt%, and tantalum to 10.0 wt%.

[0051] The use of tantalum and / or niobium increases the strength merit index and gamma prime volume fraction. increase(See Figures 3 and 6) Thus, to maximize gamma prime precipitate strengthening and thereby increase strength, it is preferred that the sum of the elements tantalum and niobium be (0.3Nb+0.15Ta)>0.1, more preferably >0.15, and even more preferably >0.2.

[0052] If high strength is desired, a minimum of 0.1 wt. % tantalum or more, preferably 0.3 wt. % or more tantalum is beneficial.

[0053] It is preferred to use niobium where lower alloy costs are preferred, and therefore it is preferred to have a minimum of 0.1 wt% niobium or more, preferably 0.3 wt% niobium or more.

[0054] The use of titanium in addition to aluminum increases the strength merit index increase (See FIG. 3.) Therefore, it is preferable to add titanium in an amount of 0.1% by weight or more, and preferably 0.3% by weight or more.

[0055] The use of titanium, tantalum and niobium in place of aluminum in the gamma prime phase results in higher ABP energies (see Equation 6). Thus, to obtain high strength, the ratio (0.5Ti+0.3Nb+0.15Ta) / Al≧0.75 is preferred, preferably ≧0.9, and more preferably ≧1.0 (Crudden et al. Acta Materialia 75(2014)356-370).

[0056] The elements platinum, palladium behave similarly to the elements tantalum, titanium and niobium, i.e. they are gamma prime forming elements which increase the anti-phase boundary energy. These elements can be optionally added to the alloy in place of the elements tantalum, titanium and niobium. The benefits may include improved resistance to high temperature corrosion. The "aluminum equivalent" for platinum and palladium requires correction factors of 0.125 and 0.225 respectively (determined from their densities relative to aluminum). However, due to the high cost of adding these elements, the addition of these elements must be limited. Thus, these elements can be present in amounts up to 1.0% by weight each, preferably limited to less than 0.5% by weight, and most preferably limited to less than 0.1% by weight, to provide an optimal balance between cost and improvement to corrosion resistance. To provide good processing by additive manufacturing, it is preferable to satisfy the following formula: JPEG0007670484000021.jpg38170Where, Pt and W Pd are the weight percentages of platinum and palladium, respectively, in the alloy.

[0057] The minimum strength requirement for the Strength Merit Index is 1050 MPa, making this alloy stronger than the strongest alloy listed in Table 3, which has a positive AM Index. Figure 3 shows how the sum of the elements Aluminum and Titanium and the sum of the elements Niobium and Tantalum affect the alloy strength (in terms of the Strength Merit Index). To achieve the required Strength Merit Index, the following equation, plotted in Figure 3, should be satisfied: More preferably, to provide a strength merit index of greater than 1050 MPa, the following formula should be satisfied: JPEG0007670484000023.jpg19170

[0058] WAl +0.5W Ti +1.5(0.3W Nb +0.15W Ta The higher the sum of W, the higher the strength merit index. Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) is preferably 3.2 or greater, more preferably 3.3 or greater, even more preferably 3.4 or greater, and most preferably 3.5 or greater, which gives a strength merit index of about 1150 MPa.

[0059] It is also a goal to limit the density of the alloy in combination with a good level of tensile strength, as determined by the strength merit index. Some elemental additions increase mechanical strength but have a negative effect on density, so the trade-off between alloy strength and alloy density must be managed. The elements in the alloy design domain that increase density the most are tungsten and tantalum. The effect on alloy density for alloys that meet the AM merit index of 0.0 or greater is shown in Figure 4. The specific strength merit index of the new alloy (calculated by dividing the strength merit index by density) is 115.8 MPa.cm, the specific strength merit index of Waspaloy. 3 .g -1 Thus, if the minimum strength merit index of the new alloy is 1050 MPa, it is preferable to provide an alloy with a density that is within the upper and lower alloy limits set forth in Table 3, such as 8.7 g / cm3, which provides an improved specific strength compared to Waspaloy. 3 It is preferred to limit the density of the alloy to less than 5.4% by weight. Thus, the tungsten content of the alloy is limited to less than 5.4% by weight, and the limit for the tantalum addition is 4.9% by weight. In order to limit the density of alloys to which tungsten and tantalum are added, it is preferred to follow the formula:

[0060] JPEG0007670484000024.jpg19170Here, f(Density) is 8.7g / cm 3 To produce alloys with densities below 5.4, rhenium and / or ruthenium can be substituted for tungsten, with the following formula: 1.1W Ta +(W W +0.92W Re +1.58W Ru ) is obtained.

[0061] As previously mentioned, by controlling the γ' volume fraction and the strength merit index, the yield stress and creep resistance of the alloy are improved. Further improvement of the alloy strength can be achieved by adding elements that partition into the face-centered cubic (FCC) matrix phase called gamma (γ). The effect of the elements on the strength of the γ phase is calculated using the solid solution merit index (SSI). The γ phase of the present invention is primarily composed of the elements molybdenum, cobalt, chromium and tungsten. Chromium does not strongly affect the solid solution strengthening of the γ phase, and the addition of chromium primarily improves the resistance of the alloy to oxidation and corrosion (Figure 12). Cobalt does not strongly affect the solid solution strengthening of the γ phase, but it does have a beneficial effect on the creep merit index, as shown in Figures 8-11. The elements molybdenum and tungsten have been found to have the strongest effect on the solid solution index.

[0062] The effect of molybdenum and tungsten on the solid solution index is shown in Figure 5. The minimum target for the solid solution index was 90 MPa, with a more preferred minimum target of 95 MPa. The change in solid solution index was related to the change in tungsten and molybdenum content according to the following equation:

[0063] JPEG0007670484000025.jpg19170 where f(SSI) is a number and W W and W Moare the weight percentages of tungsten and molybdenum, respectively, in the alloy. Tungsten can be substituted with rhenium and / or ruthenium, which changes the formula to (W w +0.92W Re +1.58W Ru )+2.1W Mo For example, to produce an SSI value of at least 90 MPa, the value of f(SSI) should be 8.7 or more. The minimum concentration of Mo+W is limited to 4.2 wt.% to achieve a satisfactory level of SSI. To produce alloys with an SSI value of at least 95 MPa, which corresponds to the highest SSI in Table 3, the value of f(SSI) is preferably 11.0 or more. Therefore, the minimum content of Mo+W is preferably greater than 5.3 wt.%, and even more preferably greater than 5.6 wt.%. As explained below with reference to Table 12, rhenium and / or ruthenium may replace tungsten, so that tungsten can be replaced by ruthenium and / or rhenium in this formula depending on the density ratio of these elements. That is, the formula becomes (W w +0.92W Re +1.58W Ru )+W Mo is 4.2 or more, preferably 5.3 or more, and even more preferably 5.6 or more. If the tungsten content is limited to 5.4 wt%, it is preferable to produce an alloy with 1.6 wt% or more molybdenum to produce an alloy with SSI of more than 90 MPa, and it is more advantageous to produce an alloy with a molybdenum content of 2.7 wt% or more to produce an alloy with SSI of 95 MPa or more. Since the maximum allowable amount of molybdenum is 4.0 wt%, it is desirable to have a minimum amount of tungsten of 0.2 wt%. This means that the more expensive rhenium and ruthenium are not required. Desirably, the amount of tungsten is at least 0.7 wt%, or even at least 1.0 wt% or more, such as a minimum of 1.5 wt% or 2.0 wt%, or even a minimum of 2.6 wt%. This allows for little or no reliance on the addition of rhenium and ruthenium, as well as a reduced Mo content (helping with hot corrosion resistance).

[0064] From Figure 6, it can be seen that to produce an alloy that can be easily processed by additive manufacturing, it is preferable to limit the γ' volume fraction to 0.30 at the equilibrium temperature of 900 °C. The most preferred AM index value W Al +0.5W Ti +0.3W Nb +0.15W Ta Based on a γ' volume fraction of ≦3.0, the most preferred γ' volume fraction is limited to 0.23. This limit is plotted in Figure 7. The effect of γ' volume fraction and creep merit index on creep resistance (1000 hour creep rupture temperature when tested at 137 MPa) is shown in Figure 7. Increasing both parameters improves creep resistance. The locations of alloys listed in Table 3 with positive values ​​of AM Index are shown in Figure 7. To produce an alloy with improved creep resistance over Waspaloy, a predicted 1000 hour creep rupture life of greater than 850°C is preferred. To improve creep resistance compared to Waspaloy, the Creep Merit Index should be 5.3x10 that of Waspaloy. -15 m -2 The creep merit index for the alloy system listed in Table 2 is preferably greater than 8.5x10 -15 m -2 s (see Figure 8-11). -15 m -2 The elemental additions required to achieve a creep figure of merit exceeding s are discussed in the following section with reference to Figures 6 and 8-11. To produce an alloy with improved creep resistance, it is preferred that the γ' volume fraction is higher than that of Waspaloy, and for an equilibrium temperature of 900°C, the γ' volume fraction of the new alloy is preferably 0.18-0.30, and more preferably 0.18-0.23. More preferably, for a better combination of creep resistance and AM processing, the γ' volume fraction of the new alloy is 0.20-0.23 for an equilibrium temperature of 900°C. This is confirmed with reference to Figure 6.

[0065] An alloy with the desired γ' fraction of 0.18 to 0.3 is produced if the aluminum, titanium, niobium, and tantalum contents must satisfy the following constraints: JPEG0007670484000026.jpg19170where f(γ') is a value in the range of 2.65 to 3.5. When f(γ') is a value in the range of 2.8 to 3, alloys with γ' fractions of 0.20 to 0.23 are produced, which provides an improved combination of high creep strength and AM processing. Thus, to satisfy the f(γ') constraint, the (0.5W Ti +0.3W Nb +0.15W Ta ) / W Al ≦1.5, the minimum aluminum content in the alloy should be 1.0 wt.%. To produce an alloy with a γ' fraction of 0.20-0.23 and f(γ') of 2.8-3, the preferred minimum aluminum content should be 1.1 wt.%. Creep resistance can be further improved by increasing the γ' fraction, so f(γ') should be 2.9 or higher. Therefore, the minimum aluminum content is preferably 1.2 wt.%.

[0066] The effect of cobalt, tungsten and molybdenum on the creep merit index is shown in Figure 8-11. It can be seen that these elements have a beneficial effect on improving creep resistance. The creep merit index target is 5.3x10 -15 m -2s. To produce an alloy with a good balance between density and creep resistance, the tungsten content is limited to 5.4 wt.%. The molybdenum content in the alloy is kept below 4.0 wt.% to reduce the susceptibility to hot corrosion. To further improve hot corrosion resistance, the molybdenum content is preferably limited to 3.8 wt.% or less, more preferably 3.5 wt.% or less, and even more preferably 3.0 wt.% or less. Figure 11 shows the effect of cobalt and tungsten on creep resistance when molybdenum is limited to 4.0 wt.%, which provides the best creep resistance in the preferred molybdenum range. When the range of tungsten for density (maximum 5.4 wt.%) is considered, a minimum concentration of 8.9 wt.% cobalt provides a sufficiently high creep merit index. Higher creep resistance is preferably provided by alloys containing 14.0 wt.% cobalt or more. More preferably, the minimum content of cobalt in the alloy is 15.6% by weight, since this, with 4.0% by weight of molybdenum, results in a 7.0x10 -15 m -2 This is because alloys are produced that have creep merit indices greater than 7.0x10 s, which provide a good level of creep resistance when the γ' volume fraction is at the lower recommended limit of 0.20. The cobalt content, for example, is 7.0x10 s when the molybdenum addition is at the lower end of the recommended limit of 1.6 wt% (Figure 9). -15 m -2More preferably, it is greater than 17.1 wt.% so that a creep merit index of 10 ... -15 m -2 A creep index of merit of 0.05% is required, and therefore the preferred lower limit of tungsten is 1.8 wt.% which is achieved with 20% cobalt. Most preferably, the tungsten content is greater than 3.1 wt.% so that high creep resistance combined with improved hot corrosion resistance due to low levels of molybdenum can be achieved (FIG. 9).

[0067] The elements rhenium, ruthenium, and iridium behave similarly to tungsten; that is, they are gamma-forming elements that improve the creep merit index. These elements may be added to the alloy optionally, provided that the sum of the elements tungsten, rhenium, ruthenium, and iridium is equal to or less than the equivalent of 5.4% tungsten in terms of density. The addition of these elements significantly increases the creep response of the alloy compared to tungsten (due to its much slower diffusivity), but significantly increases the cost due to the high cost of the elements. Based on the tungsten content (5.4% or less by weight), which controls the density, the elements may be added to a level that improves creep resistance without increasing the alloy density above the preferred tungsten content. To do this, a density-based coefficient relative to tungsten is calculated for each alloy. The coefficients for rhenium, ruthenium, and iridium are 0.92, 1.58, and 0.85, respectively. Thus, it is preferred that the maximum rhenium content is 5.0 wt%, the ruthenium content 8.5 wt% and the iridium content 4.6 wt%. Additions of these elements are more preferably limited to less than 3.0 wt%, even more preferably less than 2.0 wt%, and most preferably less than 1.5 wt% due to element cost.

[0068] FIG. 12 provides a map relating alloy composition to the main oxides formed at high temperatures. The alloy needs to form oxides, mainly chromia (Cr2O3) and alumina (Al2O3), to prevent oxygen ingress which would degrade the material's properties. The addition of 1 is necessary to allow the formation of these protective oxides. Based on the minimum content of aluminum in the alloy (1 wt%), a minimum content of chromium is preferred to be 10.8 wt% (FIG. 12) so that chromia scale forms even at the lowest levels of aluminum concentration. Most preferably, the chromia content should be greater than 15.0 wt%, as it has a strong effect of improving oxidation resistance and also provides very good resistance to high temperature corrosion.

[0069] The maximum concentration of chromium is controlled to ensure the maintenance of microstructural stability and the formation of undesirable topologically close packed (TCP) phases such as sigma (σ) and mu (μ) phases. The main elements that lead to the formation of TCP phases are molybdenum, tungsten and chromium. Figure 13 shows the effect of these elements on the Md value of the gamma matrix phase. A low Md value is preferred as it improves the microstructural stability. The Md value is preferably limited to 0.92 so that the stability is comparable to other alloys listed in Table 3. Thus, considering a minimum requirement of 4.2 wt% for the sum of the elements molybdenum and tungsten (Mo+W), it is beneficial that the chromium content is less than 20.6 wt%, more preferably less than 19.2 wt% (based on the preferred Mo+W=5.3 wt%), more preferably less than 17.6 wt%, since this results in improved stability (Md=0.91) when Mo+W=4.2 wt%, and most preferably less than 16.6 wt%, since this results in a stability value of 0.91 (Md=0.91) when Mo+W=5.3 wt%, resulting in an optimal balance between strength stability and oxidation / corrosion resistance (FIG. 13). Preferably, the Mo+W content is less than 10.8 wt%, which achieves good stability (Md=0.91) when the chromium level is equal to 10.8 wt%. More preferably, Mo+W is less than 6.6 wt % because it provides good stability (Md=0.91) when the chromium content is 15.0 wt % or more.

[0070] Additions of carbon, boron and zirconium are necessary to provide strength to the grain boundaries. This is particularly beneficial for the creep and fatigue properties of the alloy. The concentration of carbon should be in the range of 0.02% to 0.35% by weight. To reduce cracking in the AM process, low levels of carbon are preferred, therefore a content of less than 0.2% or less than 0.15% by weight is preferred, more preferably less than 0.1% by weight. Since boron can separate into a liquid phase during solidification and cause liquation cracking during the AM process, the concentration of boron should be in the range of 0.001 to 0.2% by weight, preferably less than 0.03% by weight, more preferably less than 0.02% by weight. The concentration of zirconium should be in the range of 0.001% to 0.5% by weight, preferably less than 0.01% by weight, more preferably less than 0.006% by weight.

[0071] When the alloy is produced, it is beneficial to be substantially free of unavoidable impurities. These impurities may include elemental sulfur (S), manganese (Mn) and copper (Cu). Elemental sulfur should be lower than 0.003% by weight (30 PPM by mass). Manganese is an unavoidable impurity limited to 0.25% by weight, and preferably limited to less than 0.1% by weight. Copper (Cu) is an unavoidable impurity, preferably limited to 0.5% by weight. The presence of more than 0.003% by weight of sulfur can cause embrittlement of the alloy, and sulfur also segregates to the alloy / oxide interface formed during oxidation. For this reason, the level of sulfur is preferably less than 0.001% by weight. Vanadium, an unavoidable impurity, adversely affects the oxidation behavior of the alloy and is therefore preferably limited to 0.5% by weight, and preferably limited to less than 0.3% by weight, and most preferably limited to less than 0.1% by weight. This segregation can lead to increased spalling of the protective oxide scale. When the concentrations of these unavoidable impurities exceed specified levels, problems with product yield and degradation of the material properties of the alloy are expected.

[0072] The addition of hafnium (Hf), up to 0.5 wt.%, more preferably up to 0.2 wt.%, is beneficial to counteract unavoidable impurities in the alloy and also to provide strength. Hafnium is a strong carbide former and can provide additional grain boundary strengthening.

[0073] Additions of the so-called "reactive elements" yttrium (Y), lanthanum (La), and cerium (Ce) are beneficial up to levels of 0.1 wt.% because they improve the adhesion of protective oxide layers such as Cr2O3. These reactive elements can "mop-up" tramp elements such as sulfur, which segregate to the alloy / oxide interface and weaken the bond between the oxide and the substrate, resulting in oxide spallation. Additions of up to 0.5 wt.% silicon (Si) can be beneficial, and at levels up to 0.5 wt.%, silicon additions to nickel-base superalloys have been shown to be beneficial for oxidation properties. In particular, silicon segregates to the alloy / oxide interface and improves the adhesion of the oxide to the substrate. This reduces oxide spallation and improves oxidation resistance.

[0074] Based on the description of the invention presented in this section, the broad scope of the invention is set forth in Table 4. EXAMPLES

[0075] Table 4 lists example compositions (AMNi-1 - AMNi-3) from the present invention. The calculated properties of these new alloys in Table 4 are compared to currently used alloys in Table 5. The rationale for these alloy designs is explained.

[0076] [Table 4]

[0077] [Table 5]

[0078] The alloys AMNi-1 - AMNi-3 of the examples included in the present invention have an improved balance of mechanical properties (tensile strength and creep strength) compared to current alloys with AM indexes calculated to be positive. The result is an improved combination of mechanical strength and processability using additive manufacturing compared to the known alloys listed (N80A, N90, Waspaloy). In particular, the tensile strength (in terms of strength merit index) is improved by 93-109 MPa (compared to Waspaloy), an improvement of 8.5-10%. Furthermore, the creep resistance of the alloy is improved relative to Waspaloy by increasing the γ' volume fraction as well as increasing the creep merit index (Figure 7). The increase in γ' volume fraction and creep merit index combined improves the creep rupture life at 25°C compared to Waspaloy (Figure 7). These improvements are achieved at roughly comparable cost and density to other alloy properties, such as known alloys (N80A, N90, Waspaloy).

[0079] [Table 6]

[0080] [Table 7]

[0081] Table 6 shows the (0.5W Ti +0.3W Nb +0.15W Ta ) / W Al Example compositions are shown where the ratio of elements is varied between 0.98 and 1.98 for the relationship between 0.98 and 1.98. Calculated properties of these alloys showing the effect of this ratio are given in Table 7. It can be seen that increasing the ratio increases the tensile strength (in terms of the strength merit index) compared to the baseline alloy AMNi-3. This is achieved with little change in other properties such as density and cost. The ratio (0.5W Ti +0.3W Nb +0.15W Ta ) / WAl Increasing the amount of ε phase in the alloy can result in the formation of undesirable phases (ε) that reduce the ductility of the alloy. Low levels of ε phase, less than 5%, can be tolerated. (0.5W Ti +0.3W Nb +0.15W Ta ) / W Al The alloy AMNi-6, with a ε fraction of 1.48, has an ε fraction that exceeds this limit, indicating that it is beneficial to limit the ratio to less than 1.5. Ti +0.3W Nb +0.15W Ta ) / W Al The alloy AMNi-5 with a melting point of 1.28 has a fraction of ε phase of less than 5%. Ti +0.3W Nb +0.15W Ta ) / W Al = 1.125, shows very limited ε phase formation but has improved strength compared to the baseline alloy AMNi-3.

[0082] [Table 8]

[0083] [Table 9]

[0084] Table 8 shows example compositions where the cobalt content is varied between 11.5 and 29.5 wt% in alloy AMNi-3. The calculated properties of these alloys showing the effect of cobalt are listed in Table 9. It can be seen that decreasing the cobalt content (AMNi-10- AMNi-12) compared to the baseline alloy AMNi-3 reduces the creep resistance (in terms of creep merit index). However, the creep merit index target is still achieved. The decrease in cobalt limits the change in other properties such as γ' volume fraction and tensile strength (in terms of strength merit index). The reduction in cobalt is also favorable to lower the cost of the alloy and increase its stability by lowering the Md value. Increasing the cobalt content (AMNi-13- ​​AMNi-18) compared to the baseline alloy AMNi-3 increases the creep merit index and improves the creep resistance. The effect on γ' volume fraction and tensile strength is limited. Increasing the cobalt increases the cost of the alloy. At the 29.5 wt.% level, the alloy approaches the limit of stability (Md≦0.92), and therefore, to control the cost and stability of the alloy, it is preferred to keep the cobalt content below 29.5 wt.%.

[0085] [Table 10]

[0086] [Table 11]

[0087] Table 10 shows example compositions where the chromium content is varied between 9.0 and 23.0 wt% in alloy AMNi-3. Calculated properties of these alloys showing the effect of chromium are listed in Table 11. It can be seen that reducing the chromium content (AMNi-19- AMNi-24) compared to the baseline alloy AMNi-3 improves the microstructural stability (in terms of reduced Md values) of the alloy. Reducing the level of chromium reduces the oxidation resistance because higher levels of chromium promote more protective oxides. As chromium is reduced, there is a limited change in other properties such as γ' volume fraction and tensile strength (in terms of strength merit index). Increasing the chromium content (AMNi-25- AMNi-26) compared to the baseline alloy AMNi-3 improves the oxidation resistance. There is a limited effect on γ' volume fraction and tensile strength. Increasing the chromium content beyond the 21.0 wt% level takes the alloy beyond the stability limit (Md ≤ 0.92). Therefore, to control the cost and stability of the alloy, it is preferred to keep the cobalt content below 21.0 wt.%. The more preferred chromium range of 15.0-19.5 wt.% provides the best balance of oxidation resistance and microstructural stability.

[0088] [Table 12]

[0089] [Table 13]

[0090] Table 12 shows example compositions in which tungsten is replaced by rhenium and ruthenium in amounts between 0.46 and 4.6 wt.% and 0.79 and 7.9 wt.% respectively in alloy AMNi-3. Calculated properties of these alloys showing the effect of using rhenium and ruthenium in place of tungsten are given in Table 13.

[0091] It can be seen that the replacement of the tungsten content with rhenium (AMNi-27-AMNi-36) compared to the baseline alloy AMNi-3 has a significant effect on the creep resistance (measured in creep merit index). At a rhenium content of 4.2 wt.%, the creep resistance is improved by 30°C compared to AMNi-3 (Figure 7). This results in an alloy with a creep temperature of 882°C, an improvement of more than 50°C compared to Waspaloy. Rhenium is denser than tungsten, but the ratio W W :0.92W Re By substituting rhenium for tungsten according to the present invention, density is not adversely affected. The improvement in performance obtained by substituting rhenium for tungsten comes at a significant cost increase. For this reason, it is preferable to limit the use of rhenium. The addition of rhenium also has the effect of improving the stability of the alloy (in terms of a lower Md value).

[0092] It can be seen that the creep resistance (in terms of the creep merit index) is significantly improved when replacing the tungsten content (AMNi-37 -AMNi-46) with ruthenium compared to the baseline alloy AMNi-3. For a ruthenium content of 7.9 wt.%, the creep resistance is improved by 50°C compared to AMNi-3 (Figure 7). This results in alloys with a creep temperature of 903°C, an improvement of more than 75°C compared to Waspaloy. Ruthenium has a lower density than tungsten, but at the ratio W W :1.58W Ru The density of the alloy is maintained by substituting ruthenium for tungsten according to the ratio W W :1.58W Ru The use of tungsten in place of ruthenium below 0.1% is beneficial because of both improved creep resistance and density. The performance improvement obtained by substituting ruthenium for tungsten comes at a significant cost increase. For this reason, it is preferable to limit the use of ruthenium.

[0093] [Table 14]

[0094] [Table 15]

[0095] Table 14 shows example compositions where the nickel content of alloy AMNi-3 is directly replaced by iron from 1.0 to 6.0 wt%. Calculated properties of these alloys showing the effect of iron are listed in Table 15. The main benefit of adding iron is the residual element remaining after recycling / remelting of the alloy scrap. Higher tolerance to iron addition improves the recyclability of the alloy. It can be seen that increasing the iron content (AMNi-47-AMNi-53) compared to the baseline alloy AMNi-3 reduces the microstructural stability of the alloy (in terms of increasing Md value). The iron content should be limited to 6.0 wt% or less to stay below the stability limit (Md≦0.92), which is the target for the stability of the alloy. The change in other properties such as γ' volume fraction, tensile strength (in terms of strength merit index) or creep resistance (in terms of creep merit index) due to the addition of iron is limited. The alloy preferably contains less than 2 wt.% iron, which provides a better balance between microstructural stability and recyclability.

[0096] [Table 16]

[0097] [Table 17]

[0098] Table 16 shows example compositions with fixed levels of cobalt, chromium, molybdenum, and tungsten and varying amounts of aluminum, niobium, tantalum, and titanium. Alloy AMNi-3 is shown for comparison. Calculated properties of these alloys showing their effect on the AM Index are listed in Table 17.

[0099] In comparison to the baseline alloy AMNi-3, increasing the amount of γ'-phase formers (AMNi-54- AMNi-56) increases the susceptibility to cracking during AM processing (in terms of AM index). However, the target of AM index is still achieved. From Figure 14, it can be seen that when the AM index is -1.00 or higher, no cracking occurs during AM manufacturing, but when the AM index is less than -1.00, cracking occurs during AM manufacturing. The samples in Figure 14 are 10 mm x 10 mm x 10 mm cube samples, which were produced using selective laser melting powder-bed method to evaluate the processability of selected nickel-base superalloys by additive manufacturing. The samples were produced under the same conditions from argon gas atomised alloy powder (+15-45 μm) processed under argon atmosphere (<0.1% O2). To best represent how the machine will behave in a manufacturing situation, a 2.2 J / mm 2 A fixed energy density of 0.01 and a layer thickness of 30 μm were selected. After a final 1 μm diamond polish, metallographic samples were prepared by cutting parallel to the build direction exposing the XZ plane. Figure 14 shows typical photomicrographs from an optical microscope after applying histogram-derived thresholding.

[0100] As the AM index decreases, there is a significant impact on other properties such as γ' phase volume fraction and tensile strength (in terms of the strength merit index). The result is an improved combination of mechanical strength and processability using additive manufacturing compared to known alloys such as IN939 (AM index -1.26). It can be seen that increasing the AM index (at fixed levels of cobalt, chromium, molybdenum, and tungsten) reduces the microstructural stability of the alloy (in terms of increasing Md value).

Claims

1. In weight percentage, 1.0 to 3.5 weight percent aluminum; 0.0 to 3.6 weight percent titanium; 0.0 to 6.0 wt. % niobium; 0.1 to 4.9 weight percent tantalum; 0.0 to 5.4 weight percent tungsten; 0.0 to 4.0 weight percent molybdenum; 8.9 to 30.0 wt. % cobalt; 10.8 to 20.6 wt. % chromium; 0.02 to 0.35 weight percent carbon; 0.001 to 0.2 weight percent boron; 0.001 to 0.5 wt. % zirconium; 0.0 to 5.0 wt. % rhenium; 0.0 to 8.5 wt. % ruthenium; 0.0 to 4.6 wt. % iridium; 0.0 to 0.5 wt. % vanadium; 0.0 to 1.0 wt. % palladium; 0.0 to 1.0 weight percent platinum; 0.0 to 0.5 wt. % silicon; 0.0 to 0.1 wt. % yttrium; 0.0 to 0.1 wt. % lanthanum; 0.0 to 0.1 wt. % cerium; 0.0 to 0.003 wt. % sulfur; 0.0 to 0.25 wt. % manganese; 0.0 to 6.0 wt. % iron; 0.0 to 0.5 wt. % copper; 0.0 to 0.5 weight percent hafnium; the balance being nickel and unavoidable impurities; A nickel-base alloy composition satisfying the formula: 4.2≦(W W +0.92W Re +1.58W Ru )+W Mo 2.65≦W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦4.0 and 3.1≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta ) In the above formula, W W , W Nb , W Ta , W Ti , W Mo , W Al , W Re , and W Ru are the weight percentages of tungsten, niobium, tantalum, titanium, molybdenum, aluminum, rhenium, and ruthenium, respectively, in the alloy.

2. 2. The nickel-base alloy composition of claim 1, wherein the nickel-base alloy composition satisfies the following formula: (0.5W Ti +0.3W Nb +0.15W Ta ) / W Al ≦1.5 In the above formula, W Nb , W Ta , W Ti , and W Al , are the weight percentages of niobium, tantalum, titanium, and aluminum, respectively, in the alloy.

3. 3. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: 1.1W Ta +(W W +0.92W Re +1.58W Ru )≦5.4 In the above formula, W Ta , W W , WRe, and WRu are the weight percentages of tantalum, tungsten, rhenium, and ruthenium, respectively, in the alloy.

4. 4. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: 8.7≦(W W +0.92W Re +1.58W Ru )+2.1W Mo In the above formula, W W , WRe, WRu, and WMo are the weight percentages of tungsten, rhenium, ruthenium, and molybdenum, respectively, in the alloy.

5. 5. The nickel-based alloy composition according to claim 1, wherein the sum of the elements molybdenum and tungsten is in the range of 5.3 to 9.4 weight percent.

6. The nickel-based alloy composition according to any one of claims 1 to 5, comprising, by weight percentage, 1.0 to 3.0 wt. % aluminum.

7. The nickel-based alloy composition according to any one of claims 1 to 6, comprising, by weight percentage, 0.2 to 4.9 wt.% tungsten.

8. The nickel-based alloy composition according to any one of claims 1 to 7, comprising, by weight percentage, 1.6 to 4.0 wt. % molybdenum.

9. 9. The nickel-base alloy composition of claim 1, comprising, by weight percentage, up to 3.1 wt.% titanium.

10. The nickel-based alloy composition according to any one of claims 1 to 9, comprising, by weight percentage, 15.6 to 25.0 wt.% cobalt.

11. The nickel-based alloy composition according to any one of claims 1 to 10, comprising, by weight percentage, 10.8 to 19.2 wt.% chromium.

12. The nickel-based alloy composition according to any one of claims 1 to 11, comprising, by weight percentage, 0.02 to 0.2 wt.% carbon.

13. The nickel-based alloy composition according to any one of claims 1 to 12, comprising, by weight percentage, 0.001 to 0.03 wt.% boron.

14. The nickel-based alloy composition according to any one of claims 1 to 13, comprising, in weight percentages, 0.001 to 0.01 wt. % zirconium.

15. 15. The nickel-base alloy composition of claim 1, comprising, by weight percentage, up to 5.1 wt.% niobium.

16. 16. The nickel-base alloy composition of any one of claims 1 to 15, having a microstructure with a gamma prime volume fraction of 0.18 to 0.30 at 900°C.

17. The nickel-base alloy composition of claim 1, wherein the nickel-base alloy composition satisfies the following formula: W W +0.92W Re +1.58W Ru +0.85W Ir ≦5.4

18. 18. The nickel-based alloy composition of claim 1, comprising, by weight percentage, up to 3.0 wt.% rhenium and / or ruthenium and / or iridium.

19. 19. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: 3.2≦W Al +0.5W Ti +1.5(0.3W Nb +0.15W Ta )

20. 20. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: W Al +0.5W Ti +0.3W Nb +0.15W Ta ≦3.5

21. 21. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: 5.3≦(W W +0.92W Re +1.58W Ru )+WMo

22. 22. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: 4.2≦WW+W Mo

23. 22. The nickel-based alloy composition of claim 1, wherein the nickel-based alloy composition satisfies the following formula: WW+W Mo ≦4.2

24. 24. The nickel-base alloy composition of claim 1, comprising, by weight percentage, up to 3.8 wt.% molybdenum.

25. 25. The nickel-base alloy composition of claim 1, comprising, by weight percentage, at least 0.3 wt.% tantalum.

26. 26. The nickel-base alloy composition of claim 1, comprising, by weight percentage, at least 0.1 wt.% niobium.

27. 27. The nickel-base alloy composition of claim 1, comprising, by weight percentage, at least 0.1 wt.% titanium.

28. 28. The nickel-base alloy composition of claim 1, comprising, by weight percentage, at least 0.2 wt.% tungsten.

29. 29. The nickel-base alloy composition of claim 1, wherein the nickel-base alloy composition satisfies the following formula: (0.5W Ti +0.3W Nb +0.15W Ta ) / W Al ≧0.75

30. 10. The nickel-based alloy composition of claim 1, comprising, by weight percentage, at least 14.0 wt.% cobalt.

31. Contains 10.8% by weight or more of chromium, and Mo 7. The nickel-base alloy composition of claim 1, wherein +WW is 9.4 wt.% or less.

32. In terms of weight percentage, it contains 15.0 weight percent or more of chromium and W Mo 23. The nickel-base alloy composition of any one of claims 1 to 22, wherein +WW is less than 6.6 wt.%.

33. 32. The nickel-base alloy composition of claim 1, comprising, by weight percentage, greater than or equal to 15.0 wt.% chromium.

34. 34. A method of manufacturing an article, comprising subjecting the nickel-based alloy composition of any one of claims 1 to 33 to an additive manufacturing process to produce the article.

35. 34. An article formed from the nickel-base alloy composition of any one of claims 1 to 33.

Citation Information

Patent Citations

  • Nickel-based heat-resistant alloy

    JP2013216939A

  • HEAT TREATMENT METHOD FOR Ni-BASED ALLOY LAMINATE MOLDED BODY, MANUFACTURING METHOD FOR Ni-BASED ALLOY LAMINATE MOLDED BODY, Ni-BASED ALLOY POWDER FOR LAMINATE MOLDED BODY, AND Ni-BASED ALLOY LAMINATE MOLDED BODY

    JP2018168400A

  • Heat-resistant superalloy

    WO2011062231A1

Cited By

  • Nickel-based alloy

    JP2023166393A